Framework for assessing environmental friendly strategies with the support of simulation (2017)
The technology shift from fossil -fuelled systems to renewable energies has been romoted by governments with the purpose of decarbonising the power industry. However, rapid technology progress has prompted disruptive changes that transformed market structures. Incumbent electricity utilities, particularly those based on fossil - fuel plant, are shifting from their stable and predictable situation to confront challenges from those that offer alternative energy services. In this new environment, the industry will benefit from mid - to long - term sector foresight. This thesis studies :(i)the potential impact of renewable energy sources (RES) on electricity systems − merit order -effect and revenue erosion caused by distributed generation −, particularly, on the generation and distribution businesses, and (ii) measures to lead with the possible consequences of investments in renewable energy sources. For this purpose, a fairly detailed and ntegrated supply and demand - based system dynamics model has been built . The model disaggregates the household sector, which may generate a significant part of its lectricity using rooftop solar energy. This is illustrated by examining a utility engaged in the generation and distribution businesses in the Colombian electricity market. Simulation runs suggest that subject to policy and economic circumstances , solar rooftop generation is a major threat for utilities; while the generation business is most affected in the short - term, the distribution business is the one most im pacted in the long - term, and jointly they may induce the utility “death spiral”. Furthermore , strategies to a ddress death spiral were simulated, results indicate that under certain conditions it is possible to attain a balance between social welfare and the aversion of the utility death spiral through systemic interventions